(untitled) (Tanzania Medical Journal, 2020)
All too frequent, valuable research output and scholarly materials from expensively conducted research work in different parts of the world end up in research desks, academic libraries, and scientific journals. Muhimbili University of Health and Allied Science (MUHAS) through the Directorate of Research and Publications initiated a series of symposia that aim to disseminate the evidence generated by the researchers to the policy makers and the community. In two of the six conducted University-wide symposia in the last one year, MUHAS produced two important policy briefs summarizing the impact of MUHAS research in two important—though distinct areas of local and global health impact—Elimination of Mother to Child Transmission (EMTCT) of HIV, and Diarrhea diseases.